PENGARUH SEMANGAT KERJA, KEJELASAN PERAN, FISIK LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI UNIVERSITAS POTENSI UTAMA - Austin Alexander Parhusip (Manajemen dan Bisnis, 2019)
An organization is established because it has goals that it wants and must achieve. The importance of the role of human resources in educational institutions, human’resources’should be managed properly. Managing human resources is the duty of a manager. The word "managing" in the phrase managing human resources shows that the task of managing educational institutions such as the Main Potential University is required to be able to motivate and direct and influence so that they are able’to carry out’their duties well to support other resources within the organization.Performance Assessment is a formal and structured system that measures, assesses, and influences traits related to work, behavior, and results, including rates of absence. The focus is to find out how productive an employee or employee is and whether he can perform equally or more effectively in the future, so that employees, organizations and communities all benefit.This study aims to see’how the influence of work spirit, clarity of role, physical work environment on employee performance at the Main Potential University. In this study, data was obtained through the dissemination of assessments of employee performance at the University of Main Potential. The data analysis method used in this study is descriptive analysis which includes depicting the characteristics of respondents who become samples of research and quantitative analysis with multiple linear regression analysis and using a tool in the form of SPSS program computer software.Keywords : Spirit at work; Clarity of role; Physical work environment; Employee performance